Exclusion and inclusion in identification: regulation, displacement and data justice. Issue 1 (2nd January 2021) - Martin, Aaron; Taylor, Linnet
ABSTRACT: Around the world, regimes of identification regulate people's interactions with state and commercial institutions. These regimes promise access to resources and entitlements, while also facilitating people's visibility to states and therefore their governability. For many, proving one's identity presents no challenge; however, it is estimated that a billion people have no official proof of identity. Meanwhile, the humanitarian sector is undergoing a transformation in which digital identity, mobile connectivity and digital finance are central features. Through a data justice lens, this paper explores customer identification regimes in two country contexts in which large displaced populations are present: Uganda and Bangladesh. The two cases reveal divergent approaches to regulating refugee identification: while Uganda's policy environment has recently become more inclusive, Bangladesh's proves to be particularly restrictive. We reflect on what these cases mean for the future development of digital identity systems by the humanitarian sector and the implications for data justice.